Surgery versus cast immobilisation for adults with a bicortical fracture of the scaphoid waist (SWIFFT): a pragmatic, multicentre, open-label, randomised superiority trial. Issue 10248 (8th August 2020) - Dias, Joseph J; Brealey, Stephen D; Fairhurst, Caroline; Amirfeyz, Rouin; Bhowal, Bhaskar; Blewitt, Neil; Brewster, Mark; Brown, Daniel; Choudhary, Surabhi; Coapes, Christopher; Cook, Liz; Costa, Matthew; et al.
Summary: Background: Scaphoid fractures account for 90% of carpal fractures and occur predominantly in young men. The use of immediate surgical fixation to manage this type of fracture has increased, despite insufficient evidence of improved outcomes over non-surgical management. The SWIFFT trial compared the clinical effectiveness of surgical fixation with cast immobilisation and early fixation of fractures that fail to unite in adults with scaphoid waist fractures displaced by 2 mm or less. Methods: This pragmatic, parallel-group, multicentre, open-label, two-arm, randomised superiority trial included adults (aged 16 years or older) who presented to orthopaedic departments of 31 hospitals in England and Wales with a clear bicortical fracture of the scaphoid waist on radiographs. An independent remote randomisation service used a computer-generated allocation sequence with randomly varying block sizes to randomly assign participants (1:1) to receive either early surgical fixation (surgery group) or below-elbow cast immobilisation followed by immediate fixation if non-union of the fracture was confirmed (cast immobilisation group). Randomisation was stratified by whether or not there was displacement of either a step or a gap of 1–2 mm inclusive on any radiographic view. The primary outcome was the total patient-rated wrist evaluation (PRWE) score at 52 weeks after randomisation, and it was analysed on an available case intention-to-treat basis. This trial is registered with the ISRCTN registry, ISRCTN67901257, and is no longer recruiting, but long-term follow-up is ongoing. Findings: Between July 23, 2013, and July 26, 2016, 439 (42%) of 1047 assessed patients (mean age 33 years; 363 [83%] men) were randomly assigned to the surgery group (n=219) or to the cast immobilisation group (n=220). Of these, 408 (93%) participants were included in the primary analysis (203 participants in the surgery group and 205 participants in the cast immobilisation group). 16 participants in the surgery group and 15 participants in the cast immobilisation group were excluded because of either withdrawal, no response, or no follow-up data at 6, 12, 26, or 52 weeks. There was no significant difference in mean PRWE scores at 52 weeks between the surgery group (adjusted mean 11·9 [95% CI 9·2–14·5]) and the cast immobilisation group (14·0 [11·3 to 16·6]; adjusted mean difference −2·1 [95% CI −5·8 to 1·6], p=0·27). More participants in the surgery group (31 [14%] of 219 participants) had a potentially serious complication from surgery than in the cast immobilisation group (three [1%] of 220 participants), but fewer participants in the surgery group (five [2%]) had cast-related complications than in the cast immobilisation group (40 [18%]). The number of participants who had a medical complication was similar between the two groups (four [2%] in the surgery group and five [2%] in the cast immobilisation group). Interpretation: Adult patients with scaphoid waist fractures displaced by 2 mm or less should have initial cast immobilisation, and any suspected non-unions should be confirmed and immediately fixed with surgery. This treatment strategy will help to avoid the risks of surgery and mostly limit the use of surgery to fixing fractures that fail to unite. Funding: National Institute for Health Research Health Technology Assessment Programme.